2010
DOI: 10.1002/jbmr.166
|View full text |Cite
|
Sign up to set email alerts
|

Do proton pump inhibitors decrease calcium absorption?

Abstract: Proton pump inhibitors (PPIs) increase osteoporotic fracture risk presumably via hypochlorhydria and consequent reduced fractional calcium absorption (FCA). Existing studies provide conflicting information regarding the direct effects of PPIs on FCA. We evaluated the effect of PPI therapy on FCA. We recruited women at least 5 years past menopause who were not taking acid suppressants. Participants underwent three 24-hour inpatient FCA studies using the dual stable isotope method. Two FCA studies were performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
85
0
9

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(97 citation statements)
references
References 46 publications
3
85
0
9
Order By: Relevance
“…Calcium carbonate (40% elemental calcium) or calcium citrate (21% elemental calcium) are most commonly prescribed and should be taken with meals. The solubility of calcium carbonate is dependent upon acidification, and achlorhydria may impede absorption; however, this is controversial (43). Patients on a proton pump inhibitor or elderly subjects with achlorhydria should be at least initially treated with calcium citrate, which does not require an acidic environment for absorption.…”
Section: Acute Management Of Hypoparathyroidismmentioning
confidence: 99%
“…Calcium carbonate (40% elemental calcium) or calcium citrate (21% elemental calcium) are most commonly prescribed and should be taken with meals. The solubility of calcium carbonate is dependent upon acidification, and achlorhydria may impede absorption; however, this is controversial (43). Patients on a proton pump inhibitor or elderly subjects with achlorhydria should be at least initially treated with calcium citrate, which does not require an acidic environment for absorption.…”
Section: Acute Management Of Hypoparathyroidismmentioning
confidence: 99%
“…However, information about the relationship with serum 25(OH)D is limited. Recently published research showed no change in serum 25(OH)D after omeprazol therapy, but this study sample consisted of healthy young people and they used omeprazole for only 30 days (36).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our inability to assess vitamin D status and nutritional intake of magnesium and calcium limits the conclusion that detrimental effect on serum calcium levels is definitely attributed to PPIs. Ca carbonate consumed under fasting condition a decade ago, two other studies assessed calcium absorption using dual-stable calcium isotopes and found no changes in fractional calcium absorption, thus concluding no effect of PPI on calcium absorption and metabolism (26,27). Similarly, a recent study of Sharara et al (28) concluded no measurable effect of PPI intake on calcium metabolism.…”
Section: Discussionmentioning
confidence: 99%